2016
DOI: 10.1038/srep32617
|View full text |Cite
|
Sign up to set email alerts
|

Depinning of domain walls in permalloy nanowires with asymmetric notches

Abstract: Effective control of the domain wall (DW) motion along the magnetic nanowires is of great importance for fundamental research and potential application in spintronic devices. In this work, a series of permalloy nanowires with an asymmetric notch in the middle were fabricated with only varying the width (d) of the right arm from 200 nm to 1000 nm. The detailed pinning and depinning processes of DWs in these nanowires have been studied by using focused magneto-optic Kerr effect (FMOKE) magnetometer, magnetic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To overcome these challenges, several ideas were proposed and tested; such as relying on natural defect [5052] and creating physically notches [53][54][55][56][57][58][59][60][61]. Other non-geometrical schemes such as modifying locally the magnetic properties of the ferromagnetic nanowire [6267] using exchange coupling [62,63], metal diffusion [64] or ionimplantation [65,66] were also investigated.…”
Section: Although Tremendous Efforts Have Been Dedicatedmentioning
confidence: 99%
“…To overcome these challenges, several ideas were proposed and tested; such as relying on natural defect [5052] and creating physically notches [53][54][55][56][57][58][59][60][61]. Other non-geometrical schemes such as modifying locally the magnetic properties of the ferromagnetic nanowire [6267] using exchange coupling [62,63], metal diffusion [64] or ionimplantation [65,66] were also investigated.…”
Section: Although Tremendous Efforts Have Been Dedicatedmentioning
confidence: 99%
“…Artificial nanowires (NW) with naturally formed defects of different geometries acting as trapping sites have also been investigated using both numerical simulation and experimental observations [4,[31][32][33]. Several studies have also reported that experimentally creating notches using lithography helps to block or pin DWs [5,6,[34][35][36][37][38][39][40][41]. These artificial constrictions work as pinning sites for DWs due to their higher pinning potential than that of other pinning sites such as * rachid@squ.edu.om defects in the NWs.…”
Section: Introductionmentioning
confidence: 99%
“…The critical challenge for DW memory application is the control of DW position at the nanoscale regime. In previous studies, many groups have reported that the creation of notches along the wire is a successful method for DW pinning by creating an energy potential [19][20][21].…”
Section: Introductionmentioning
confidence: 99%